(untitled) (Journal of Mathematical Study, 2018)
Using an integral identity for a once differentiable mapping, this paper establishes Hadamard's integral inequalities for s-convex and s-concave mappings. In particular, our results improve and extend some known ones in the literature. Finally, these inequalities are applied to special means.